Solids, colloids, and the hydrolysis of tetravalent uranium in chloride media - Grambow, B.; Müller, R.; Schild, D.; Gaona, X. (Frontiers in Nuclear Engineering, 2023)
The mechanism of formation of UO2+y from U(VI) and U(IV) containing aqueous solution (1 M NaCl) and the solubilities of the precipitates were studied under well controlled reducing conditions as a function of pH, particle size and supersaturation. The results show that tetramer and colloid formation are critical initial steps. Precipitation is not growth-controlled, but appears to be nucleation-controlled, with critical nuclei dimension of one unit cell of UO2. Precipitates were always crystalline, amorphous UO2 was not observed.